Study of Nonlocal Boundary Value Problems of Non-Integer Order Hybrid Differential Equations - Samina; Kamal Shah; Rahmat Ali Khan (Matrix Science Mathematic, 2017)
We study sufficient conditions for existence and uniqueness of solutions to boundary value problems (BVPs) for fractional hybrid differentialequations(FHDEs) of the form where I=[0,1],σ,θ ∈(1,2] and δ,ω∈(0,1) . We use hybrid fixed point theorem due to Dhage and develop adequateresults for existence of solutions to the proposed system of (FHDEs). We also provide a numerical problem to demonstrate our main results.